On the History of the Photo Studio “Russian Photography in Vilnius”: “Paleographic Album of Northwest Russian Writing and Printing” - Morozova, Nadežda (Literatūra, 2025)
In 1864–1867, Ivan I. Petrov had a photo studio in Vilnius, called “Russian Photography in Vilnius”. Two photo albums created in this studio were known: the album “Suprasl Monastery” (54 pictures, now, 52 have been preserved) and the album of photographs of the exhibits of the Vilnius Museum of Antiquities (64 pictures; the present location is unknown). Recently, an album “Palaeographic Album of Northwest Russian Writing and Printing” was discovered at Vilnius University Library. This album is designed in the same way as the Suprasl Monastery album. This made it possible to identify the palaeographic album as a work coming from Petrov’s photo studio. The album consists of 9 sheets of 6 Cyrillic written monuments created or used in the Grand Duchy of Lithuania, mainly in the 16th century. All of them came to the attention of the Vilnius Educational District in the second half of the 19th century.
Keywords: “Russian Photography in Vilnius”; photographer Ivan I. Petrov; paleographic album; Cyrillic literary monuments; Vilnius Public Library